2019
DOI: 10.35940/ijrte.d6842.118419
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tech Savvy Trait AS A Base for Profiling Impulse Buyers

Dr .Ramesh Kumar Chaturvedi*,
Shivang Dwivedi

Abstract: Impulse buying behavior is a sudden spontaneous urge of the consumer to make unplanned purchase after seeing the product in the retail outlet. Such type of behavior involves purchasing without much thinking. A number of studies have been conducted in the past regarding consumer decision making. This study has its base in the form of tech savvy consumers. Impulse purchase behavior for tech savvy consumers has not been studied much in the past; neither any scale has been developed specifically for such kind of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This is one of very few studies that have sought to identify and profile distinct segments of impulse buyers. It benefits from and builds on the related work of Ciunova-Shuleska (2012) and Dwivedi and Chaturvedi (2019). The segments captured in the three studies are substantially different from one another – not a surprising outcome, given that they drew upon different conceptual frameworks (leading to the selection of widely varying constructs) and represented different shopping contexts in three different countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is one of very few studies that have sought to identify and profile distinct segments of impulse buyers. It benefits from and builds on the related work of Ciunova-Shuleska (2012) and Dwivedi and Chaturvedi (2019). The segments captured in the three studies are substantially different from one another – not a surprising outcome, given that they drew upon different conceptual frameworks (leading to the selection of widely varying constructs) and represented different shopping contexts in three different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Kalla (2016) observed that a tendency to seek surprises induced impulse buying in a quest for novelty. Dwivedi and Chaturvedi's (2019) segmentation study found consumer innovativeness to be a characteristic attribute in two of their three clusters. Granero et al (2016) observed a relationship between novelty seeking and compulsive buying behavior in the clinical domain.…”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations